2012
DOI: 10.14778/2336664.2336678
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sort-merge joins in main memory multi-core database systems

Abstract: Two emerging hardware trends will dominate the database system technology in the near future: increasing main memory capacities of several TB per server and massively parallel multi-core processing. Many algorithmic and control techniques in current database technology were devised for diskbased systems where I/O dominated the performance. In this work we take a new look at the well-known sort-merge join which, so far, has not been in the focus of research in scalable massively parallel multi-core data process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 20 publications
(52 reference statements)
1
119
0
Order By: Relevance
“…Comparing sort-merge and hash join algorithms has been the topic of recent work for joins on multi-core systems and efficient algorithms for both strategies have been proposed [1,3,4,5,9,27,30]. Kim et al [27] concluded that although modern hardware currently favors hash join algorithms, future processors with wider Single-InstructionMultiple-Data (SIMD) instructions would significantly speed up sort-merge joins.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing sort-merge and hash join algorithms has been the topic of recent work for joins on multi-core systems and efficient algorithms for both strategies have been proposed [1,3,4,5,9,27,30]. Kim et al [27] concluded that although modern hardware currently favors hash join algorithms, future processors with wider Single-InstructionMultiple-Data (SIMD) instructions would significantly speed up sort-merge joins.…”
Section: Related Workmentioning
confidence: 99%
“…Kim et al [27] concluded that although modern hardware currently favors hash join algorithms, future processors with wider Single-InstructionMultiple-Data (SIMD) instructions would significantly speed up sort-merge joins. Albutiu et al [1] presented a sort-merge join optimized for multi-socket NUMA machines. Their implementation reaches a throughput of 160M tuples/second on 64 cores.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Ré focus on statistical analytics and conclude that awareness of the core topology can improve performance by an order of magnitude compared to the state-of-the-art systems [72]. On the other hand, the majority of the proposals that target building NUMA-aware data management systems focus on removing memory bandwidth bottlenecks for analytical applications and specifically devising efficient join and sorting algorithms that minimize data movement [3,6,42,51]. However, OLTP workloads cannot saturate memory bandwidths and their main problem is ensuring efficient synchronization among threads [52].…”
Section: Performance On Multisocket Multicoresmentioning
confidence: 99%
“…Thus, the throughput also heavily depends on the workload, adding another dimension to the design space and making the optimal deployment decision nearly "black magic." 3 An oversimplified estimation of the throughput of a shared-nothing deployment as a function of the number of distributed transactions is given by the following. If T local is the throughput of the shared-nothing system when each instance executes only local transactions, and T distr is the throughput of a shared-nothing deployment when every transaction requires data from more than one database instances, then the total throughput T is:…”
Section: Abundant Hardware Parallelismmentioning
confidence: 99%